Ubiquitous Absence - Pötzsch Holger (Nordicom Review, 2013)
The present article provides an analysis of the narrative and technical devices through which contemporary war films frame audience engagement with characters. It compiles and systematizes a wide set of empirical findings and exemplifies these through brief, illustrative readings of a selection of films. Combining Smith’s approach to film reception with insights from Laclau and Mouffe’s theory of discourse, the article argues for the significance of the identified audio-visual rhetoric for political discourse and practice.